2018
DOI: 10.1002/cplu.201700493
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Biocompatible Scaffolds through the Design of Elastin‐Based Short Peptides

Abstract: A small library of short peptides has been synthesized based upon the repeat tetrapeptide sequence Gly‐Val‐Ala‐Pro (GVAP) which is found in the hydrophobic domain of tropoelastin. Of the five peptides synthesized, four formed self‐supporting hydrogels with similar secondary structures. The ability to tune the mechanical properties of the resultant hydrogels was demonstrated, and this is understood in relation to fiber bundling. Finally, the cytotoxicity of these elastin‐based short peptide hydrogels towards He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
(85 reference statements)
0
5
0
Order By: Relevance
“…Similar to the behavior of thermoresponsive synthetic polymers, a characteristic property of ELPs is their lower critical solution temperature (LCST)-like behavior (also termed an inverse transition temperature), which endows ELPs with the ability to be used as building blocks for the assembly of nanostructures. A wide variety of studies have demonstrated the versatility of ELP design and resulting transition temperature ,, and the application of these principles to the production of hydrogel matrices and drug delivery vehicles. While these studies illustrate the versatility of the ELPs as self-assembling building blocks, essentially all of the ELPs employed are recombinamers with tens or even hundreds of pentapeptide repeats. Short synthetic ELPs (peptides) on their own have been rarely used as bulk materials for biomedical applications, possibly due to their relatively high transition temperature, , although recent studies suggest the utility of the conjugation of short ELPs to polymers and dendrimers to control LCST-like behavior and self-assembly as well as the impact of protecting groups on the thermally induced transitions of short ELPs …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to the behavior of thermoresponsive synthetic polymers, a characteristic property of ELPs is their lower critical solution temperature (LCST)-like behavior (also termed an inverse transition temperature), which endows ELPs with the ability to be used as building blocks for the assembly of nanostructures. A wide variety of studies have demonstrated the versatility of ELP design and resulting transition temperature ,, and the application of these principles to the production of hydrogel matrices and drug delivery vehicles. While these studies illustrate the versatility of the ELPs as self-assembling building blocks, essentially all of the ELPs employed are recombinamers with tens or even hundreds of pentapeptide repeats. Short synthetic ELPs (peptides) on their own have been rarely used as bulk materials for biomedical applications, possibly due to their relatively high transition temperature, , although recent studies suggest the utility of the conjugation of short ELPs to polymers and dendrimers to control LCST-like behavior and self-assembly as well as the impact of protecting groups on the thermally induced transitions of short ELPs …”
Section: Introductionmentioning
confidence: 99%
“…Short synthetic ELPs (peptides) on their own have been rarely used as bulk materials for biomedical applications, possibly due to their relatively high transition temperature, 38,39 although recent studies suggest the utility of the conjugation of short ELPs to polymers and dendrimers to control LCST-like behavior and self-assembly 45−49 as well as the impact of protecting groups on the thermally induced transitions of short ELPs. 50 In our previous work, we demonstrated that this limitation can be easily overcome by simply conjugating short ELPs with a triple-helix-forming CLP. 51 The resulting ELP−CLP bioconjugate exhibited a remarkable reduction in the inverse transition temperature (T t ) of the ELP domain upon formation of the CLP triple helix, so that nanostructures can be formed under aqueous conditions in a temperature range of relevance for biomaterials applications.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The self-assembly of biomolecules have received significant attention as a facile route to fabricate bioinspired scaffolds with porous, three-dimensional (3D) architectures, that have increasingly well-understood mechanisms to control their formation [1,2,3]. Nevertheless, for effective cell culture and tissue growth, significant functionalization is required to truly exploit their promise as biomaterials; the engineering of biomaterial scaffolds should to not only mechanically support cells, but also actively modulate cellular activities [4,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Among these peptides, Fmoc-FGVAPF shows a lateral aggregation phenomenon. [28] The sequence APF is also present in collagen and could be a key motif in its hierarchical organization.…”
Section: Introductionmentioning
confidence: 99%